Merging optimization and control in power systems physical and cyber restrictions in distributed frequency control and beyond - Liu, Feng; Wang, Zhaojian; Zhao, Changhong; Yang, Peng (IEEE Press, 2022)
Merging Optimization and Control in Power SystemsA novel exploration of distributed control in power systems with insightful discussions of physical and cyber restrictionsIn Merging Optimization and Control in Power Systems an accomplished team of engineers deliver a comprehensive introduction to distributed optimal control in power systems. The book re-imagines control design within the framework of cyber-physical systems with restrictions in both the physical and cyber spaces, addressing operational constraints, non-smooth objective functions, rapid power fluctuations caused by renewable generations, partial control coverage, communication delays, and non-identical sampling rates.This book bridges the gap between optimization and control in two ways. First, optimization-based feedback control is explored. The authors describe feedback controllers which automatically drive system states asymptotically to specific, desired optimal working points.
A novel exploration of distributed control in power systems with insightful discussions of physical and cyber restrictionsIn Merging Optimization and Control in Power Systems an accomplished team of engineers deliver a comprehensive introduction to distributed optimal control in power systems. The book re-imagines control design within the framework of cyber-physical systems with restrictions in both the physical and cyber spaces, addressing operational constraints, non-smooth objective functions, rapid power fluctuations caused by renewable generations, partial control coverage, communication delays, and non-identical sampling rates.This book bridges the gap between optimization and control in two ways. First, optimization-based feedback control is explored. The authors describe feedback controllers which automatically drive system states asymptotically to specific, desired optimal working points. Second, the book discusses feedback-based optimization. . - Leveraging the philosophy of feedback control, the authors envision the online solving of complicated optimization and control problems of power systems to adapt to time-varying environments.Readers will also find:* A thorough argument against the traditional and centralized hierarchy of power system control in favor of the merged approach described in the book* Comprehensive explorations of the fundamental changes gripping the power system today, including the increasing penetration of renewable and distributed generation, the proliferation of electric vehicles, and increases in load demand* Data, tables, illustrations, and case studies covering realistic power systems and experiments* In-depth examinations of physical and cyber restrictions, as well as the robustness and adaptability of the proposed modelPerfect for postgraduate students and researchers with the prerequisite knowledge of power system analysis, operation, and dynamics, convex optimization theory, and control theory, . - Merging Optimizati
Keywords: Elektronik, Elektrotechnik, Nachrichtentechnik